Nitrogen‐Doped Hierarchical Porous Carbon through One‐Step Activation of Bean Curd for High‐Performance Supercapacitor Electrode. Issue 12 (23rd April 2018) - Li, Qiang; Wu, Xiaozhong; Zhao, Yi; Miao, Zhichao; Xing, Lingbao; Zhou, Jin; Zhao, Jinping; Zhuo, Shuping
Abstract: New nitrogen‐doped hierarchical porous carbons (HPCs) with large surface areas were prepared from bean curd through a one‐step impregnation activation method at 750 °C with CH3 COOK as an activating agent. The porous carbons were characterized by a variety of techniques such as N2 ‐sorption analysis, scanning electron microscope (SEM), transmission electron microscope (TEM), and X‐ray photoelectron spectroscopy. The results show that there are numerous macropores with a pore size of ∼200 nm observed by SEM and TEM as well as micropores probed by N2 ‐sorption analysis, indicating a hierarchical porous structure for these carbon materials. The effect of activating agent dosage on the porous structure of carbon was carefully investigated. The Brunauer‐Emmett‐Teller specific surface area and nitrogen content for the optimized carbon are 2180 m 2  g −1 and 2.62 at%, respectively. As evidenced by electrochemical measurements, the as‐prepared carbon has a good capacitive performance and the specific capacitance is calculated to be 284 F g −1 at a current density of 0.1 A g −1 in KOH electrolyte. More importantly, this carbon could deliver a high capacitance up to 118 F g −1 at a very high current density of 30 A g −1 due to its hierarchical porous structure, which will facilitate the ion transfer under high current density. Our research highlights the potential application of these HPCs as high‐performance electrode materials for electric double‐layer capacitors. Abstract : CH3 COOK‐ed bean curd : Nitrogen‐doped hierarchical porous carbons (HPCs) with large surface areas are prepared from bean curd through a one‐step impregnation activation method at 750 °C with CH3 COOK as an activating agent. The as‐prepared carbons have a hierarchical porous structure, heteroatom doping, large surface area, and short micropore channel on the macropore walls. Electrochemical measurements show that all HPCs have excellent capacitive performance. Our research highlights the potential application of these HPCs as high‐performance electrode materials for electric double‐layer capacitors.